2014
DOI: 10.1161/circulationaha.113.002416
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibition Blunts Ischemia/Reperfusion Injury by Inducing Cardiomyocyte Autophagy

Abstract: Background Reperfusion accounts for a substantial fraction of the myocardial injury occurring with ischemic heart disease. Yet, no standard therapies are available targeting reperfusion injury. Here, we tested the hypothesis that SAHA, a histone deacetylase (HDAC) inhibitor FDA-approved for cancer treatment, will blunt reperfusion injury. Methods and Results Twenty-one rabbits were randomized into 3 groups: a) vehicle control, b) SAHA pretreatment (one day prior and at surgery), and c) SAHA treatment at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
289
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(302 citation statements)
references
References 46 publications
10
289
1
2
Order By: Relevance
“…5 E and F). Interestingly, and in contrast to recent reports (23,24), left ventricular mass was unchanged (Fig. 5G).…”
Section: Saha Treatment Reduces Aggregate Levels and Improves Cardiaccontrasting
confidence: 97%
See 2 more Smart Citations
“…5 E and F). Interestingly, and in contrast to recent reports (23,24), left ventricular mass was unchanged (Fig. 5G).…”
Section: Saha Treatment Reduces Aggregate Levels and Improves Cardiaccontrasting
confidence: 97%
“…The therapeutic potential of HDAC inhibition has also been explored for different cancers and the HDAC inhibitor, SAHA, is FDA-approved to treat cutaneous T-cell lymphoma. Importantly, it was recently shown that SAHA induces autophagy in cardiomyocytes (24), but the underlying mechanism was not determined. The effects of modulating HDAC activity likely are a function of the specific disease, cell type, and dosing protocols used, and should be completely understood to expand the therapeutic reach of HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an ischemic insult, the developed pressure is reduced and the end diastolic pressure elevates ( Figure 1B). When the rats are administered a known preconditioning agent such as the class I and IIb HDAC inhibitor SAHA (vorinostat) 18 prior to excising the heart, the reduction in developed pressure and the elevation of end diastolic pressure associated with ischemia reperfusion injury are attenuated ( Figure 1C). Other measures of left ventricular function, such as the rate of pressure generation (dP/dt max ), the rate of pressure relaxation (-dP/dt max ), and the rate pressure product (RPP) can be directly obtained or calculated from the software output (Figure 2).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Class I and class IIa HDAC inhibitors have shown promise in ameliorating the effects of adverse tissue remodeling post-MI. Several comprehensive in vivo studies have shown that pan-HDAC inhibitors such as suberoylanilide acid, TSA, and valproic acid not only reduce infarct scar area but also improve cardiac function after an MI (22,49,72,76).…”
Section: Class II Hdacs In Cardiovascular Diseasementioning
confidence: 99%